Study on the Validity of Property Donated by One Spouse to the Third Party - Dong, Sijun (International Journal of Social Sciences and Public Administration, 2025)
During marriage, the problem that one spouse donates property to a third party due to extramarital affairs has a long history, and there are different views and arguments in practice and academic circles. This paper discusses the validity of the contract and the change of property right of one spouse's gift to the third party separately, starting with the judgment of the validity of the gift contract, and comprehensively analyzes the consideration factors of invalidity of the contract violating the principle of public order and good customs from the angle of the application of the principle of public order and good customs, so as to explore whether the validity of the contract of one spouse's gift to the third party is valid or not; In the behavior of one spouse's disposition of the donated property to a third party, the change of property ownership is taken as the breakthrough point and analysis context, and the issue of ownership and return of the donated property is reorganized based on the different results of the validity judgment of the gift contract, in order to improve the judgment of the validity of the property donated by one spouse to a third party.